Zeolites as Carriers of Antitumor Ribonuclease Binase - Khojaewa, Vera; Lopatin, Oleg; Zelenikhin, Pavel; Ilinskaya, Olga (Frontiers in Pharmacology, 2019)
Natural and synthetic zeolites have many applications in biomedicine and nutrition. Due to its properties, zeolites can absorb therapeutically active proteins and release them under physiological conditions. In this study we tested the clinoptilolite, chabazite and natrolite ability to be loaded by antitumor ribonuclease binase and the cytotoxicity of the complexes obtained. We found the optimal conditions for binase loading into zeolites and established the dynamic of its release. Cytotoxic effects of zeolite-binase complexes towards colorectal cancer CaCo2 cells were characterized after 24h and 48h of incubation with cells using MTT-test. Zeolites were toxic itself and reduced cells viability by 30% (clinoptilolite ), 40% (chabazite) and 70% (natrolite) after 48 h of incubation but complexes of clinoptilolite as well as chabazite with binase demonstrated always enhanced toxicity (up to 57% and 60% for clinoptilolite and chabazite, respectively) in comparison to binase and zeolites separately. Our results contribute to the perspective development of binase-based complexes for therapy of colorectal cancer for or the treatment of malignant skin neoplasms when a complexes can be used in pasty form.